PENGEMBANGAN MEDIA FLIPBOOK DIGITAL PADA PEMBELAJARAN SASTRA MATERI FABEL KELAS II SEKOLAH DASAR - Roma Deswita Devy Purba; Mulyahati, Bunga; Maisarah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Literature instruction on fables in second-grade elementary school is still dominated by the use of print media, resulting in a lack of variety in instruction and suboptimal use of digital media. Therefore, there is a need for engaging instructional media that are tailored to the characteristics of the students. This study aims to design and develop a digital flipbook as an instructional tool for teaching fables in second-grade elementary school and to determine the feasibility and practicality of the developed media. This study is a research and development (R&D) project using the ADDIE model, which includes the stages of analyze, design, develop, implement, and evaluate. The study was conducted at Langsa Lama Public Elementary School with 19 second-grade students as research subjects. Data collection techniques included interviews, observations, questionnaires, and documentation. The results of this study indicate that the digital flipbook media was developed using the Canva application and supported by the Heyzine platform, integrating text, images, and audio elements tailored to the students’ characteristics. The results of the content and language expert validation achieved a percentage of 97%, categorized as “highly valid,” while the media expert validation achieved a percentage of 86%, also categorized as “highly valid.” The average media suitability percentage was 91.5%, categorized as “highly valid.” The results of the teacher response questionnaire yielded a percentage of 100% in the “very practical” category, and the student response yielded a percentage of 99% in the “very practical” category, resulting in an average practicality percentage of 99.5% in the “very practical” category. Thus, the digital flipbook media developed is deemed highly valid and highly practical, making it suitable for use in teaching fables in second-grade elementary school literature classes.